The long-term effect of elexacaftor/tezacaftor/ivacaftor on cardiorespiratory fitness in adolescent patients with cystic fibrosis: a pilot observational study - Nela Stastna; Lenka Hrabovska; Pavel Homolka; Lukas Homola; Michal Svoboda; Kristian Brat; Libor Fila (BMC Pulmonary Medicine, 2024)
Abstract Background Physical activity is a crucial demand on cystic fibrosis treatment management. The highest value of oxygen uptake (VO2peak) is an appropriate tool to evaluate the physical activity in these patients. However, there are several other valuable CPET parameters describing exercise tolerance (Wpeak, VO2VT1, VO2VT2, VO2/HRpeak, etc.), and helping to better understand the effect of specific treatment (VE, VT, VD/VT etc.). Limited data showed ambiguous results of this improvement after CFTR modulator treatment. Elexacaftor/tezacaftor/ivacaftor medication improves pulmonary function and quality of life, whereas its effect on CPET has yet to be sufficiently demonstrated. Methods We performed a single group prospective observational study of 10 adolescent patients with cystic fibrosis who completed two CPET measurements between January 2019 and February 2023. During this period, elexacaftor/tezacaftor/ivacaftor treatment was initiated in all of them. The first CPET at the baseline was followed by controlled CPET at least one year after medication commencement. We focused on interpreting the data on their influence by the novel therapy. We hypothesized improvements in cardiorespiratory fitness following treatment. We applied the Wilcoxon signed-rank test. The data were adjusted for age at the time of CPET to eliminate bias of aging in adolescent patients. Results We observed significant improvement in peak workload, VO2 peak, VO2VT1, VO2VT2, VE/VCO2 slope, VE, VT, RQ, VO2/HR peak and RR peak. The mean change in VO2 peak was 5.7 mL/kg/min, or 15.9% of the reference value (SD ± 16.6; p= 0.014). VO2VT1 improved by 15% of the reference value (SD ± 0.1; p= 0.014), VO2VT2 improved by 0.5 (SD ± 0.4; p= 0.01). There were no differences in other parameters. Conclusion Exercise tolerance improved after elexacaftor/tezacaftor/ivacaftor treatment initiation. We suggest that the CFTR modulator alone is not enough for recovering physical decondition, but should be supplemented with physical activity and respiratory physiotherapy. Further studies are needed to examine the effect of CFTR modulators and physical therapy on cardiopulmonary exercise tolerance.